PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN STATUS PEGAWAI TERHADAP KEPUASAN KERJA KARYAWAN DI PT ABC - Theresia Budi Ningsih; Meifida Ilyas (Pasca Sarjana Universitas Satya Negara Indonesia, 2023)
Every employee has expectation to obtain job satisfaction. Job satisfaction is influenced by several factors, including compensation, leadership and employee status. This study aims to determine whether there is an influence of compensation, leadership and employee status to job satisfaction. Research data obtained by distributing questionnaires. The sample in this study were employees at PT ABC with 90 respondents. Data analysis method using t test, F test and multiple linear regression analysis. The results of SPSS 25 data processing show that compensation has a significant effect on job satisfaction (result 0.330), leadership has a significant influence on job satisfaction (result 0.393) and employee status has a significant effect on job satisfaction (result 0.461). The results of the analysis show that the three variables have a significant effect on job satisfaction. But the highest influence on job satisfaction is employee status.